تأثير متطلبات التحول الرقمي (التقنية والبشرية) على الابتكار وتعزيز الميزة التنافسية في المصارف التجارية الليبية - سالم عبد الكافي, أشرف; ذياب محمد عمر , عازة (Dirasat in Economics and Business, 2026)
This study aims to examine the impact of digital transformation on innovation and competitiveness in Libyan commercial banks. The descriptive-analytical method was employed to achieve the objectives of the study. Data were collected through a structured questionnaire distributed to a sample consisting of managers, deputy managers, department heads, unit supervisors, auditors, and accountants working in commercial banks located in Sirte, Libya. A total of 62 questionnaires were distributed to the targeted sample. Several statistical techniques were utilized, including arithmetic means, standard deviations, relative weight, relative importance, and Cronbach’s Alpha to test the reliability of the data. Hypotheses were tested using stepwise multiple regression analysis. The study yielded several findings, the most significant of which is the existence of a statistically significant effect of the requirements of digital transformation—namely, human and technological requirements—on both innovation and competitive advantage in the sampled Libyan commercial banks.